A peculiar segmented flow microfluidics for isoquercitrin biosynthesis based on coupling of reaction and separation. (October 2015) - Gong, An; Gu, Shuang-Shuang; Wang, Jun; Sheng, Sheng; Wu, Fu-An
Graphical abstract: Highlights: A segmented flow microreactor containing "buffer-ionic liquid/solvent" was proposed. Isoquercitrin yield of 101.7 ± 2.6% using the microreactor was achieved in 20 min. The best reaction temperature of hesperidinase decreased from 40 to 30 °C. Reaction rate was improved to 4-fold than that in a continuous flow microreactor. Hesperidinase could be efficiently reused 5 times in a segmented flow microreactor. Abstract: A segmented flow containing a buffer-ionic liquid/solvent in a micro-channel reactor was applied to synthesize isoquercitrin by the hesperidinase-catalyzed selective hydrolysis of rutin, based on a novel system of reaction coupling with separation. Within the developed microchannel reactor with one T-shaped inlet and outlet, the maximum isoquercitrin yield (101.7 ± 2.6%) was achieved in 20 min at 30 °C and 4 μL/min. Compared with a continuous-flow reactor, reaction rate was increased 4-fold due to a glycine–sodium hydroxide:[Bmim][BF4 ]/glycerol triacetate (1:1, v/v) system that formed a slug flow in microchannel and significantly increased mass transfer rates. The mass transfer coefficient significantly increased and exhibited a linear relationship with the flow rate. Hesperidinase could be efficiently reused at least 5 times, without losing any activity. The bonding mechanism and secondary structure of hesperidinase indicated that hesperidinase had a greater affinity to rutin at a production rate of 4 μL/min in this segmented flow microreactor.